Customer Perception on Adoption of Quick Response (QR) Code Payment in Nepal - Wagle, Sudip (Journal of Economics and Management, 2024)
The Quick Response (QR) code payment system has grown popularity in recent years. This study aims to examine the impact of customer perception on adoption of QR code payment in Nepal. Descriptive and causal comparative research design has employed with structured questionnaire survey administered to 385 banks customers in Nepal. This study analyze the relationships and impact between the variables by using pearson correlation and regression analysis. The findings reveal positive and significant impact of Knowledge about QR Code Perceived Cost on adoption of QR code and Ease of Use while Trust and Security have insignificant impact on customer perception. The findings of this study may offer valuable insights to banks customers, policymakers, and the future researchers, aiding the value of QR code payment on cusomer satisfaction. This study offers a unique contribution by exploring how the QR code payment enhance banking transaction with customer satisfaction in the context of Nepal, where only the limited research has been conducted.